Marek's disease virus-1 unique gene LORF1 is involved in viral replication and MDV-1/Md5-induced atrophy of the bursa of Fabricius. - Chenyi Bao; Jun Chu; Qi Gao; Shasha Yang; Xiaoyu Gao; Wenwen Chen; Fuchun Yang; Fei Jiang; Chenxi Tong; Mingyi Lei; Linlin Jiao; Jitong Li; et al. (PLoS Pathogens)
Marek's disease virus (MDV), an alphaherpesvirus, causes severe immunosuppression and T cell lymphomas in chickens, known as Marek's disease (MD), an economically important poultry disease primarily controlled by vaccination. Importantly, it also serves as a comparative model for studying herpesvirus-induced tumor formation in humans. MDV encodes more than 100 genes, most of which have unknown functions. MDV LORF1 is unique to serotype I MDV (MDV-1), lacking homologs in other herpesviruses, and has not been explored yet. To this end, an infectious bacterial artificial chromosome (BAC) harboring the complete genome of the MDV-1 very virulent strain Md5 was generated, and the rescued rMd5 maintained biological properties similar to the parental virus both in vitro and in vivo. Subsequently, rMd5ΔLORF1, a recombinant Md5 virus deficient in pLORF1 expression, was generated by a frameshift mutation in the LORF1 gene. Chickens infected with rMd5ΔLORF1 exhibited a lower mortality rate and delayed bursal atrophy than those infected with the parental rMd5 and the revertant virus (rMd5-reLORF1). Consistently, viral loads of rMd5ΔLORF1 were obviously lower than those of rMd5 or rMd5-reLORF1 in the bursa, but not in the spleen. Importantly, we found that pLORF1 deficiency impairs viral replication in bursal B cells. Furthermore, we showed that pLORF1 associated with the cellular membrane, interacted with MDV structural proteins, and exhibited punctate colocalization with tegument or capsid proteins in the cytoplasm. Taken together, this study demonstrates for the first time that the MDV-1 unique gene LORF1 is involved in MDV-induced bursal atrophy but not in tumor formation.